A genome‐wide CRISPR screen identifies the CCT chaperonin as a critical regulator of vesicle trafficking. Issue 2 (6th January 2023) - Chen, Yongtian; Kang, Jing; Zhen, Ru; Zhang, Liyang; Chen, Caiyong
Abstract: Vesicle trafficking is a fundamental cellular process that controls the transport of various proteins and cargos between cellular compartments in eukaryotes. Using a combination of genome‐wide CRISPR screening in mammalian cells and RNAi screening in Caenorhabditis elegans, we identify chaperonin containing TCP‐1 subunit 4 (CCT4) as a critical regulator of protein secretion and vesicle trafficking. In C. elegans, deficiency of cct‐4 as well as other CCT subunits impairs the trafficking of endocytic markers in intestinal cells, and this defect resembles that of dyn‐1 RNAi worms. Consistent with these findings, the silencing of CCT4 in human cells leads to defective endosomal trafficking, and this defect can be rescued by the dynamin activator Ryngo 1–23. These results suggest that the cytosolic chaperonin CCT may regulate vesicle trafficking by promoting the folding of dynamin in addition to its known substrate tubulin. Our findings establish an essential role for the CCT chaperonin in regulating vesicle trafficking, and provide new insights into the regulation of vesicle trafficking and the cellular function of the cytosolic chaperonin.